Recent Advances in Diesel-Biodiesel Blended with Nano-Additive as Fuel in Diesel Engines: A Detailed Review - Ahmed Sule; Zulkarnain Abdul Latiff; Mohammed Azman Abbas; Ibham Veza; Anthony C. Opia (Universitas Muhammadiyah Magelang, 2022)
Global emission of gases has increased rapidly due to higher combustion of fossil fuels arising from increasing world population which has led to a greater number of manufacturing industries and ”˜on-road vehicle (ORV)’ users. Researchers have attributed cause of global warming to gases emissions which correspondingly lead to climate change with devastating repercussions. Currently, climate change is a general issue and world leaders have been tasked to cut down emissions of gases that directly affect the ecosystem and influence climate change. Biodiesel which is an alternative to fossil fuels face many challenges and to tackle some limitations with biodiesel researchers blends biodiesels in various proportional ratio to diesel fuel. This paper, therefore, concentrates on reviewing the use of additives specifically nano-additives by researchers recently to alter and boost desired characteristics in diesel-biodiesel fuel; it also examines the synthesis of nano-additives; challenges, and advances made. This paper further analysed, reviewed, and compared recent results from nano-additive use with respect to emissions, fuel consumption, brake thermal efficiency, and engine power, establishes the merits and demerits of diverse nano-additives, and finally presents a conclusive opinion on nano-additive usage with diesel fuels in diesel engines.